Challenges and Recent Advances in High Capacity Li‐Rich Cathode Materials for High Energy Density Lithium‐Ion Batteries. Issue 50 (26th March 2021) - He, Wei; Guo, Weibin; Wu, Hualong; Lin, Liang; Liu, Qun; Han, Xiao; Xie, Qingshui; Liu, Pengfei; Zheng, Hongfei; Wang, Laisen; Yu, Xiqian; Peng, Dong‐Liang
Abstract: Li‐rich cathode materials have attracted increasing attention because of their high reversible discharge capacity (>250 mA h g −1 ), which originates from transition metal (TM) ion redox reactions and unconventional oxygen anion redox reactions. However, many issues need to be addressed before their practical applications, such as their low kinetic properties and inefficient voltage fading. The development of cutting‐edge technologies has led to cognitive advances in theory and offer potential solutions to these problems. Herein, a recent in‐depth understanding of the mechanisms and the frontier electrochemical research progress of Li‐rich cathodes are reviewed. In addition, recent advances associated with various strategies to promote the performance and the development of modification methods are discussed. In particular, excluding Li‐rich Mn‐based (LRM) cathodes, other branches of the Li‐rich cathode materials are also summarized. The consistent pursuit is to obtain energy storage devices with high capacity, reliable practicability, and absolute safety. The recent literature and ongoing efforts in this area are also described, which will create more opportunities and new ideas for the future development of Li‐rich cathode materials. Abstract : The practical applications of Li‐rich cathode materials, especially Li‐rich Mn‐based (LRM) cathodes, are hindered by their inherent shortcomings. In this case, the recent understanding of complex reaction mechanisms, the novel modification methods, and the corresponding development trends are comprehensively reviewed. Additionally, other branches and the future opportunities of the Li‐rich cathode materials are also summarized.